Comprehensive Approach To Rheumatic Fever and Rheumatic Heart Disease Prevention and Control: The Nepalese Model - Regmi, Prakash Raj (Nepalese Heart Journal, 2016)
Rheumatic Heart Disease represents a huge public health burden in developing countries with significant morbidity and mortality. This disease is preventable and has been successfully controlled through the implementation of register-based control programs. The Nepal Heart Foundation, a non-governmental organization was the first to initiate community activities with focus on RHD prevention and control. This organization in 2007 was successful in launching the RHD prevention and control program in partnership with the government of Nepal. The Nepalese model of RHD control program is an example of a comprehensive, diagonal and register-based approach to RHD prevention and control in low resource settings. The early outcomes and impact of the program are encouraging. This paper provides an overview of the Nepalese model of RHD prevention and control program. Nepalese Heart Journal 2016; 13(2): 3-10